Prevalence of Naturally-Occurring NS5A and NS5B Resistance-Associated Substitutions in Iranian Patients With Chronic Hepatitis C Infection - Rahimi, Pooneh; Sharafi, Heidar; Bahramali, Golnaz; SajadianFard, FaridehSadat; Asadi, Nafiseh Sadat; Alavian, Seyed Moayed; Iranpur Mobarakeh, Vahid; Moravej, Seyedeh Zahra (Frontiers in Microbiology, 2021)
Background Hepatitis C virus (HCV), non-structural 5A (NS5A), and non-structural 5B (NS5B) resistance-associated substitutions (RASs) are the main causes of failure to direct-acting antiviral agents (DAAs). NS5A and NS5B RASs can occur in patients with HCV infection naturally and before exposure to DAAs. Objectives This study aimed to evaluate naturally-occurring NS5A and NS5B RASs in Iranian patients with HCV genotype 1a (HCV-1a) and -3a infections. Methods In this cross-sectional study, viral RNA was extracted from serum specimens. NS5A and NS5B regions were amplified using RT-PCR followed by DNA sequencing. The results of nucleotide sequences were aligned against reference sequences of HCV-1a and -3a and the amino acid substitutions were analyzed using geno2pheno [hcv] web application. Results Among 135 patients with hepatitis C, NS5A amino acid substitutions/RASs were identified in 26.4% and 15.9% of patients with HCV-1a and -3a infections, respectively. The identified amino acid substitutions/RASs in the NS5A region of patients with HCV-1a infection were M28T/V/I 11.1%, Q30R/H 4.2%, L31M 1.4%, and H58Y/P/C/D/Q/S/T 16.7%. Y93H substitution was not found in HCV-1a sequences. In patients with HCV-3a infection, NS5A amino acid substitutions/RASs were A30T/K 9.5%, L31F 1.6%, P58S/T/C 3.2%, Y93H 3.2%, and Y93N 3.2%. No resistance substitutions were identified in NS5B sequences from patients with HCV-1a and -3a infections. Conclusion In this study, baseline amino acid substitutions/RASs were only identified in the NS5A region in Iranian patients with HCV-1a and -3a infections, and the prevalence of these amino acid substitutions/RASs were in accordance with similar studies. There were no RASs in the HCV-1a and -3a NS5B region.